Modeling of Rail Tracks on Stone Column Reinforced Tensionless Foundations - Bhatra, Shashank; Maheshwari, Priti (Frontiers in Built Environment, 2019)
This research investigates the response of rails on geocell-stone column composite reinforced foundation beds under a moving load. Improved earth bed has been considered to respond only to compressive forces. The granular mat below the rail has been idealized as a Pasternak shear layer and geocell reinforcement as an infinite beam with finite bending stiffness. Soft soil and stone columns have been symbolized by Winkler springs of different stiffnesses. Analysis has been carried out with due consideration to viscous damping in the system. The governing differential equations have been established and simplified for general use with the help of dimensionless parameters. These equations have been solved in presence of appropriate boundary conditions by utilizing Finite difference method in combination with iterative Gauss-Seidel procedure. Inclusion of stone columns has been observed to significantly affect the onset of separation between rail and the soil layer underneath. Various parameters namely, applied load and its velocity, stiffnesses of top, bottom soil layers and stone columns, damping ratio, relative flexural rigidity, depth of placement of geocell, configuration of stone columns have been found to affect the response of soil-foundation system significantly. Improvement in the properties of soil by means of higher value of relative compressibility resulted in typical reduction of 50% in maximum deflection. It has been observed that the region of detachment reduces on increasing the depth of placement of the bottom beam. Sensitivity analysis highlighted the greater sensitivity of upward deflection as compared to the downward deflection of rail with respect to all the parameters except for relative compressibility of the soil and relative stiffness of the stone columns.